2005
DOI: 10.1007/bf02893050
|View full text |Cite
|
Sign up to set email alerts
|

Can serum Glutathione-S-transferase levels in carcinoma cervix be a predictor of radiation response?

Abstract: We conducted a pilot study wherein serum Glutathione-S-transferase levels were measured before and after radiotherapy in carcinoma cervix patients and correlated with response to treatment dudng a two-year follow-up period. Out of 17 patients who received radiotherapy, 9 showed a significant decrease (p< 0.005) while 8 showed significant increase (p< 0.004) in post radiotherapy glutathione-S-transferase values as compared to pre treatment values respectively. These patients were followed up for two years and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Prabhu et al [26] measured levels of serum GST before and after radiation. The study results showed that alterations in serum GST levels may help to predict the response to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Prabhu et al [26] measured levels of serum GST before and after radiation. The study results showed that alterations in serum GST levels may help to predict the response to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that there were no statistically important improvements in GST concentrations during therapy. However, as patients were compared based on when their condition worsened following chemoradiation, a statistically important discrepancy was found [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Prabhu et al suggested that alterations in GST serum levels might be used as a predictive tool to predict response to radiotherapy in patients with CC. 92 It was revealed that patients with CC who did not show any response after chemo/radiotherapy had significantly higher GSH levels compared with patients who responded. 93 Reduced amount of GSH might contribute to CC pathogenesis through the excessive generation of ROS.…”
Section: Diagnostic and Predictive Value Of Oxidative Stress Status In CCmentioning
confidence: 97%
“…Consequently, MAP17 or SGLT1 can be used as a useful prognostic marker for patients with CC undergoing chemo/radiotherapy. Prabhu et al suggested that alterations in GST serum levels might be used as a predictive tool to predict response to radiotherapy in patients with CC . It was revealed that patients with CC who did not show any response after chemo/radiotherapy had significantly higher GSH levels compared with patients who responded .…”
Section: Diagnostic and Predictive Value Of Oxidative Stress Status I...mentioning
confidence: 99%